Photodynamic effect of Zirconium phosphate biocompatible nano-bilayers containing methylene blue on cancer and normal cells - Hosseinzadeh, Reza (Sci Rep, 2019)
Pharmaceutical applications of methylene blue, especially as photosensitizer, have been limited due to its rapid enzymatic reduction in the biological systems. In this study nano-platelet zirconium phosphate was synthesized and its biocompatibility was evaluated. The synthesized material was considered as drug delivery vehicle for methylene blue to enhance the photodynamic therapy efficacy in human breast cancer cells. Zirconium phosphate-methylene blue nano-hybrids were characterized by X-Ray Powder Diffraction (XRPD), Scanning Electron Microscopy (SEM), and Thermo gravimetric Analysis (TGA). Biocompatibility of synthesized nano materials were studied on Hu02 human fibroblast normal cell and MDA-MB-231 human breast cancer cell. The results clarified that ZrP-MB nanoparticles could decrease the dark toxicity of free methylene blue. Photodynamic therapy using zirconium phosphate-methylene blue on MDA-MB-231 human breast cancer was evaluated by MTT assay, colony forming ability assay, AO/EB dual staining and flow cytometry detection of apoptosis. The results suggest that zirconium phosphate-methylene blue nano-hybrids significantly enhance photodynamic therapy efficacy probably via apoptosis cell death mechanism against human breast cancer cells. According to the results, zirconium phosphate nanoparticles could be suggested as a promising nano-carrier for photosensitizer delivery in photodynamic therapy.